2014
DOI: 10.1126/science.1248811
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety-like behavior in crayfish is controlled by serotonin

Abstract: Anxiety, a behavioral consequence of stress, has been characterized in humans and some vertebrates, but not invertebrates. Here, we demonstrate that after exposure to stress, crayfish sustainably avoided the aversive illuminated arms of an aquatic plus-maze. This behavior was correlated with an increase in brain serotonin and was abolished by the injection of the benzodiazepine anxiolytic chlordiazepoxide. Serotonin injection into unstressed crayfish induced avoidance; again, this effect was reversed by inject… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
187
2
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 223 publications
(213 citation statements)
references
References 29 publications
14
187
2
1
Order By: Relevance
“…This state of higher alertness is called anxiety (Blanchard and Blanchard, 1988;Belzung and Philippot, 2007;Steimer, 2011). Recently, it has been shown that anxiety-like behavior (ALB) is also observable in crustaceans (Fossat et al, 2014), allowing the study of primitive forms of anxiety and of their neurobiological correlates.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…This state of higher alertness is called anxiety (Blanchard and Blanchard, 1988;Belzung and Philippot, 2007;Steimer, 2011). Recently, it has been shown that anxiety-like behavior (ALB) is also observable in crustaceans (Fossat et al, 2014), allowing the study of primitive forms of anxiety and of their neurobiological correlates.…”
Section: Introductionmentioning
confidence: 99%
“…More particularly, the biogenic amines serotonin (5-HT) and dopamine (DA) have been involved in fear responses and anxiety in mammals (Bonhomme and Esposito, 1998;Nutt, 2001;Graeff and Zangrossi, 2010;Canteras and Graeff, 2014;Fossat et al, 2014;Zangrossi and Graeff, 2014). In crayfish and other decapods, 5-HT has been shown to control the stress response by raising secretion of crustacean hyperglycemic hormones (CHHs), leading to an increase in blood glucose (Lorenzon et al, 2005;Fossat et al, 2014). DA has been also claimed to have such a role, although conflicting observations have been reported (Sarojini et al, 1995;Zou et al, 2003;Lorenzon et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In arthropods, recent studies also described emotional-like behaviours in crayfish which were controlled by neurochemical (serotonergic) mechanisms (e.g. Fossat et al, 2014).…”
Section: The Emergence Of Consciousness In Phylogenymentioning
confidence: 99%